Cardiac miRNA expression during the development of chronic anthracycline-induced cardiomyopathy using an experimental rabbit model - Adamcova, Michaela; Parova, Helena; Lencova-Popelova, Olga; Kollarova-Brazdova, Petra; Baranova, Ivana; Slavickova, Marcela; Stverakova, Tereza; Mikyskova, Petra Sauer; Mazurova, Yvona; Sterba, Martin (Frontiers in Pharmacology, 2024)
Background: Anthracycline cardiotoxicity is a well-known complication of cancer treatment, and miRNAs have emerged as a key driver in the pathogenesis of cardiovascular diseases. This study aimed to investigate the expression of miRNAs in the myocardium in early and late stages of chronic anthracycline induced cardiotoxicity to determine whether this expression is associated with the severity of cardiac damage.Method: Cardiotoxicity was induced in rabbits via daunorubicin administration (daunorubicin, 3 mg/kg/week; for five and 10 weeks), while the control group received saline solution.Myocardial miRNA expression was first screened using TaqMan Advanced miRNA microfluidic card assays, after which 32 miRNAs were selected for targeted analysis using qRT-PCR.The first subclinical signs of cardiotoxicity (significant increase in plasma cardiac troponin T) were observed after five weeks of daunorubicin treatment. At this time point, 10 miRNAs (including members of the miRNA-34 and 21 families) showed significant upregulation relative to the control group, with the most intense change observed for miRNA-1298-5p (29fold change, p<0.01).After 10 weeks of daunorubicin treatment, when a further rise in cTnT was accompanied by significant left ventricle systolic dysfunction, only miR-504-5p was significantly (p<0.01) downregulated, whereas 10 miRNAs were significantly upregulated relative to the control group; at this time-point, the most intense change was observed for miR-34a-5p (76-fold change).Strong correlations were found between the expression of multiple miRNAs (including miR-34 and mir-21 family and miR-1298-5p) and quantitative indices of toxic damage in both the early and late phases of cardiotoxicity development. Furthermore, plasma levels of miR-34a-5p were strongly correlated with the myocardial expression of this miRNA.To the best of our knowledge, this is the first study that describes alterations in miRNA expression in the myocardium during the transition from subclinical, ANT-induced cardiotoxicity to an overt cardiotoxic phenotype; we also revealed how these changes in miRNA expression are strongly correlated with quantitative markers of cardiotoxicity.